12-2(х+1.2)=2-6х х/6-x/3=2 1/x-3=2 3(x-1)-2(2-x)=6 Каждое подробно, прошу...

12-2(х+1.2)=2-6х х/6-x/3=2 1/x-3=2 3(x-1)-2(2-x)=6 Каждое подробно, прошу...
Гость
Ответ(ы) на вопрос:
Гость
1) (x-2x)/6=2 -x/6=2 -x=12 x=-12 2) 1/x=5 5x=1 x=0,2 3) 3x-3-4+2x=6 5x=13 x=2,6
Гость
1) 12-2(х+1.2)=2-6х 12-2х-2*1,2=2-6х 6х-2х=2-12+2,4 4х=-7,6 х= -1,9 2) х/6-x/3=2  х-2х=2*6 -х=12 х=-12 3) 1/x-3=2 1/х= 2+3 1/х=5 х=1/5 4) 3(x-1)-2(2-x)=6 3х-3-4+2х=6 5х=6+3+4 5х=13 х=13/5 х=2 3/5
Не нашли ответ?
Ответить на вопрос
Похожие вопросы